Variations in cardiovascular risk factors in people with and without migration background in Germany – Results from the STAAB cohort study. (1st July 2019) - Morbach, Caroline; Gelbrich, Götz; Tiffe, Theresa; Eichner, Felizitas; Wagner, Martin; Heuschmann, Peter U.; Störk, Stefan; Frantz, S.; Maack, C.; Ertl, G.; Fassnacht, M.; Wanner, C.; et al.
Abstract: Background: About 20% of the German population have a migration background which might influence prevalence of preventable cardiovascular risk factors (CVRF). Methods: We report data of the prospective Characteristics and Course of Heart Failure Stages A-B and Determinants of Progression (STAAB) cohort study investigating a representative sample of inhabitants of the City of Würzburg, Germany, aged 30 to 79 years. Individuals without migration background were defined as follows: German as native language, no other native language, and/or born in Germany. All other participants were defined as individuals with migration background. Results: Of 2473 subjects (51% female, mean age 54 ± 12 years), 291 (12%) reported a migration background: n = 107 (37%) from a country within the EU, n = 117 (40%) from Russia, and n = 67 (23%) from other countries. Prevalence of hypertension, atherosclerotic disease, and diabetes mellitus was similar in individuals with and without migration background. By contrast, prevalence of obesity and metabolic syndrome was significantly higher in individuals with migration background, with the least favourable profile apparent in individuals from Russia (individuals without vs. with migration background: obesity 19 vs. 24%, p < 0.05; odds ratio: EU: 1.6, Russia: 2.2*, other countries: 0.6; metabolic syndrome 18 vs. 21%, p < 0.05; odds ratio: EU: 1.2, Russia: 1.7*, other countries: 1.5; * p < 0.05). Conclusion: Individuals with migration background in Germany might exhibit a higher CVRF burden due to a higher prevalence of obesity and metabolic syndrome. Strategies for primary prevention of heart failure may benefit from deliberately considering the migration background. Highlights: In a representative sample of the population of Wuerzburg, Germany, 12% of participants reported a migration background Prevalence of hypertension, atherosclerotic disease, and diabetes was equal to individuals without migration background By contrast, prevalence of obesity and metabolic syndrome was significantly higher in individuals with migration background Individuals from Russia revealed the least favourable profile of cardiovascular risk factors